Pathological effects due to metacercariae of Clinostomum piscidium migration in snakeskin gourami (Trichopodus pectoralis) in Thailand - Islam, Sk Injamamul; Rodkhum, Channarong; Taweethavonsawat, Piyanan (Frontiers in Veterinary Science, 2023)
Clinostomum spp. is a fish-borne pathogen and a digenetic trematode with a global range. Despite its zoonotic relevance, the pathogenic impact of the parasite in Thai aquaculture is currently unclear. The present study deals with the pathogenic changes that fluke causes in their host, Trichopodus pectoralis, and the molecular confirmation of the Clinostomum piscidium by targeting 18s rDNA and ITS gene. The metacercariae of C. piscidium were discovered in the body cavity of infected fish. The gross pathological examination revealed a few white migratory tracks on the surface of the liver and spleen. The migratory track showed histologically as a primary hemorrhage and necrosis of hepatic cells surrounded by a layer of macrophages and epithelioid cells, inflammatory cells, and eosinophilic granular cells in the cytoplasm of liver cells and close to the epithelial cells of the intestine. Also, the migratory track in the spleen appeared as a marked decrease of RBC (Red Blood Cell) count and changes in the necrotic tissue. Infection with this metacercaria produced hepatic tissue injury, which disrupted hepatic metabolism and decreased body weight in the fish hosts. The findings of the study suggest that the pathological effect of C. piscidium on farm T. pectoralis can cause significant economic loss by stunting fish development and predisposing fish to opportunistic pathogens in the environment. Hence, the treatment and control of C. piscidium infections are crucial for the viability of the aquaculture sector since this parasite has been found to cause pathological damage to the vital organs of fish.